Relationship between perilaryngeal pressure pain thresholds and the severity of vocal tract discomfort symptoms in vocally healthy women - Fuentes Aracena, Christopher; Biermann Orizola , Christopher; Torres Yáñez , Constanza (Revista de Investigación en Logopedia, 2024)
The purpose of this study was, in the first place to analyze the effects of vocal loading on perilaryngeal pressure pain thresholds (PPT) and vocal tract discomfort symptoms (VTDS) and secondly, to analyze the relationship between perilaryngeal PPT and the severity of VTDS. We worked with 20 vocally healthy women, who underwent a vocal loading task which consisted of reading aloud for 30 minutes at 80-90 dB. Before the loading task (T1), perilaryngeal PPT were measured and after that, perilaryngeal PPT and the severity of VTDS (T2) were evaluated. A decrease of 0.4 to 0.6 kg/cm2 in the PPT of T2 compared to T1 (p < 0.05, g > 1) was observed. The severity of VTDS was between 2 ± 1.65 and 5 ± 0.91, which correspond to burning and dryness, respectively. An inverse correlation was observed between the right thyropharyngeal region and the severity of tightness (r = -0.45, p = 0.04) and the left thyrohyoid region and the severity of aching (r = -0.71, p
Keywords: odynophonia; pressure pain threshold; vocal fatigue; vocal tract discomfort symptoms